Flexible Intelligent Robotic Equipment Ball Launcher (FIREBALL) as A Tool for Sports Training in Big Ball Games - MAJID, MOHAMMAD IRFAN; Kusuma, Donny; Wijono; Daulay, Dio; Ashadi, Kunjung; Sidik, Rizky; Jatmiko, Tutur; Fajar, Kharis; Purnomo (Proceeding of International Joint Conference on UNESA, 2025)
This research aims to develop a ball launcher or what is usually called a ball launcher. The researchers carried out the development of this tool so that the resulting tool could be more competitive with previous tools. Apart from that, this tool can be used in several sports, especially big ball sports. This tool has two dynamos for launching the ball and has a speed controller to regulate the rotation of the dynamo and this tool is designed to be flexible so that in big ball sports you can use this tool. The method used in this research is R&D (Reaserch and Development) using five stages, namely ADDIE. The results of data acquisition on tool assessment through a questionnaire are as follows: a. The assessment of the athlete's response obtained a result of 79.97%, including the "Good" category with the meaning "Used", b. The trainer's assessment obtained a result of 65.00%, including the "Enough" category with the meaning "Used (conditionally)". Based on the research results above, it can be concluded that the Flexible Intelligent Robotic Equipment Ball Launcher (FIREBALL) as a training aid for ball game sports obtained results of 72.49%, including the "Good" category with the meaning "Used" as a training aid in ball game sports.